Association of Circulating Hepatocyte Growth Factor and Risk of Incident Peripheral Artery Disease: The Multi-Ethnic Study of Atherosclerosis. (July 2020) - Garg, Parveen K.; Buzkova, Petra; Wassell, Christina L.; Allison, Matthew; Criqui, Michael; Larson, Nicholas B.; Bielinski, Suzette J.
Higher levels of hepatocyte growth factor (HGF) have been associated with the presence of peripheral arterial disease (PAD), but prospective associations are unknown. We examined the association of circulating HGF levels with incident PAD. Between 2000 and 2002, HGF was measured in 6742 Multi-Ethnic Study of Atherosclerosis participants without PAD. Incident clinical PAD, adjudicated on the basis of a positive history for the presence of disease-related symptoms or treatment, was ascertained through 2015. Incident low ankle-brachial index (ABI), defined as an ABI < 0.9 and a decline of ≥ 0.15, was assessed among 5736 individuals who had an ABI > 0.9 at baseline and ≥1 follow-up ABI measurement 3 to 10 years later. There were 116 clinical PAD and 197 low ABI events that occurred over a median follow-up of 14 and 9 years, respectively. After adjustment for demographic and clinical variables, a standard deviation increment of HGF (303 ng/L) was associated with an increased risk of clinical PAD (hazard ratio: 1.21; 95% confidence interval [CI]: 1.05-1.39) but not a low ABI (rate ratio: 1.03; 95% CI: 0.85-1.25). In conclusion, higher HGF levels were modestly associated with an increased risk of developing clinical PAD.